2023
DOI: 10.1186/s43170-023-00153-7
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen uptake and remobilization from pre- and post-anthesis stages contribute towards grain yield and grain protein concentration in wheat grown in limited nitrogen conditions

Abstract: Background In wheat, nitrogen (N) remobilization from vegetative tissues to developing grains largely depends on genetic and environmental factors. The evaluation of genetic potential of crops under limited resource inputs such as limited N supply would provide an opportunity to identify N-efficient lines with improved N utilisation efficiency and yield potential. We assessed the genetic variation in wheat recombinant inbred lines (RILs) for uptake, partitioning, and remobilization of N towards… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 63 publications
0
2
0
Order By: Relevance
“…Additionally, a significant portion of N in the grain (60-95%) may derive from remobilization, rather than soil absorption [106]. Sharma et al (2023) [107] demonstrated that the nitrogen uptake and remobilization of wheat genotypes from both the pre-and post-anthesis stages contribute to the grain yield and grain protein concentration. These findings align with our discovery that the growth stage when 20% inflorescence emerged is suitable for GPC prediction using Pléiades data.…”
Section: Predicting Gpc With Pléiades and P4m Datamentioning
confidence: 99%
“…Additionally, a significant portion of N in the grain (60-95%) may derive from remobilization, rather than soil absorption [106]. Sharma et al (2023) [107] demonstrated that the nitrogen uptake and remobilization of wheat genotypes from both the pre-and post-anthesis stages contribute to the grain yield and grain protein concentration. These findings align with our discovery that the growth stage when 20% inflorescence emerged is suitable for GPC prediction using Pléiades data.…”
Section: Predicting Gpc With Pléiades and P4m Datamentioning
confidence: 99%
“…Among the agrotechnical factors, nitrogen fertilisation has the greatest impact on the yield and chemical composition of grain. The use of nitrogen by cereals depends on genetic and environmental factors [33]. Research carried out so far shows that rye varieties use increasing doses of nitrogen unequally [34].…”
Section: Introductionmentioning
confidence: 99%